Kniha Laozi : překlad s filologickým komentářem - Sehnal, David, 1964-; Laozi; Laozi; Laozi (Varia (Univerzita Karlova. Filozofická fakulta), 2013)
This publication represents an annotated translation of one of the most important Old Chinese philosophical texts, the Book of Laozi. The translation in based on a detailed linguistic analysis of the text. The author has analyzed all of the cca 5000 words contained in the text and under each of them he presents his own understanding of its meaning and its syntactic function in the given context. In the Prologue the author explains the basic methodological principles, renders the structure of the text and gives its short philosophical characteristics. In the main part of the book, i. e. the translation with the philological notes, every chapter is introduced with a brief summary in which the author reveals its possible philosophical message. It is followed by the original Old Chinese text with marked rhyming words and its Czech translation which reflects the original in the closest possible manner. Next to it there is the philological commentary in which the author presents the results of his linguistic analysis in a transparent way. The appendix of this publication is a vocabulary of the lexemes found in Laozi. The material obtained through the linguistic analysis is organized into head words and word clusters according to individual lexemes and their syntactic functions. The volabulary is the first attempt of this kind as for the identification of Old Chinese lexemes by their syntactic paradigms.